Pola Pendidikan Ekonomi Masyarakat Nelayan Pesisir Danau yang Terintegrasi dalam Kearifan Lokal Sipakatau’ - Atirah Atirah; Muhammad Hasan (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2020)
The results of the study are interpreted that the local wisdom sipakatau which is interpreted as a sense of respect to build a form of community trust that by respecting customs rules that are believed by fishermen to have an impact on the safety and sustainability of the Lake ecosystem. Local wisdom sipakatau that forms the economic education pattern of the fishing community is obtained from fostering and exemplary that is shown hereditary in the community and within the family itself. Because the people on the coast of Lake Tempe consider that the work of fishermen is a promising job, they educate their children from patterns of habit and example, then introduce them to the customary rules that bind them as fishermen. The activity took place in the family and in the fishermen community so that their or attitude constructs them to respect their customs and customary leaders with their belief that in this way they have helped protect the natural ecosystems of the Lake for the continuation of fishermen's work. The pattern of habituation and exemplary education that is applied by respecting the customs, rules and norms of a person who forms a caring economy or caring economy, caring economy is interpreted as their concern for the lake ecosystem as a legacy and where they make a living as fishermen.